CD68-positive tumour associated macrophages, PD-L1 expression, and EBV latent infection in a high HIV-prevalent South African cohort of Hodgkin lymphoma patients - Antel, Katherine Rae (Department of Medicine, 2022)
Background and aims A higher proportion of CD68-positive tumour associated macrophages (TAMs) has been associated with poorer outcomes in HIV-negative patients with Hodgkin lymphoma (HL), but whether this is true in HIV positive patients with HL is not known. In this study, we investigated the number of CD68-positive TAMs and expression of programmed cell death-ligand 1 (PD-L1) in lymph node specimens from HL patients and correlated expression with clinical features (HIV status, disease severity and survival) and histopathological features (EBV latent positivity and subtype of HL). Methods We stained archived lymph node specimens from 77 patients diagnosed with HL for CD68 and PD-L1. Stains were graded as: CD68 low (≤25%), CD68 high (>25%), PD-L1 low (≤50%), and PD-L1 high (>50%). Expression levels were correlated with the clinical and histopathological features using bivariate and multivariate analyses. Survival was analysed by overall and progression-free survival. Results Thirty-four of the 77 included patients (44%) were HIV-positive. EBV latency was detected in 97% of HIV positive HL patients and in 14% of HIV-negative HL patients. A high CD68 score was associated with lower median haemoglobin levels (9.4 vs 11.4 g/dL; p=0.02), platelet numbers (262 vs 424 cells ×109 /L; p=0.01), and lymphocyte numbers (0.99 vs 1.70 cells ×109 /L, p=0.01) and a trend towards advanced disease (international prognostic score ≥4; hazard ratio 2.4; confidence interval 0.89–6.47; p=0.08). HIV status did not affect CD68 or PD-L1 expression. A higher proportion of CD68-positive TAMs was found in samples that were EBV-positive. HIV positivity and EBV negativity correlated with poorer survival. CD68 and PD-L1 expression were not predictive of survival. Conclusions High CD68 expression was associated with EBV positivity but not HIV positivity and did not predict adverse outcomes. PD-L1 expression was unaffected by HIV status or EBV positivity and did predict adverse outcomes.